2014
DOI: 10.5713/ajas.2013.13702
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Factors Affecting Abdominal Fat Deposition in Poultry: A Review

Abstract: The major goals of the poultry industry are to increase the carcass yield and to reduce carcass fatness, mainly the abdominal fat pad. The increase in poultry meat consumption has guided the selection process toward fast-growing broilers with a reduced feed conversion ratio. Intensive selection has led to great improvements in economic traits such as body weight gain, feed efficiency, and breast yield to meet the demands of consumers, but modern commercial chickens exhibit excessive fat accumulation in the abd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
168
2
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(185 citation statements)
references
References 120 publications
7
168
2
8
Order By: Relevance
“…Sci., 9 (3): 144-154, 2015 At present, feed restriction (Fisher, 1984) and the inclusion of dietary additives that promote lean growth at the expense of fat deposition are the two commercially successful methods in use. According to the recent review by Fouad and El-Senousey (2014), both the methods have shown a decrease in body fat, but many reports have shown negative effect on body weight.…”
Section: Introductionmentioning
confidence: 99%
“…Sci., 9 (3): 144-154, 2015 At present, feed restriction (Fisher, 1984) and the inclusion of dietary additives that promote lean growth at the expense of fat deposition are the two commercially successful methods in use. According to the recent review by Fouad and El-Senousey (2014), both the methods have shown a decrease in body fat, but many reports have shown negative effect on body weight.…”
Section: Introductionmentioning
confidence: 99%
“…In broilers, fatty acid synthesis occurs mainly in the liver, and the adipose tissue is the primary site of fat storage as triglycerides, especially the abdominal fat tissue (Huang et al, 2008;Fouad & El-Senousey, 2014). Therefore, we investigated the effect of the dietary supplementation of FCSM on lipid-related gene expression of acetyl CoA carboxylase (ACC), fatty acid synthase (FAS), lipoprotein lipase (LPL), peroxisome proliferator-activated receptor alpha (PPAR-α), and liver fatty acid-binding protein (L-FABP) in liver tissue, as well as LPL and peroxisome proliferator-activated receptor gamma (PPAR-γ) in the abdominal fat tissue of broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to high levels of fat in BSC compared to SBM, which is about twice the amount of energy compared to carbohydrates. Since broilers primarily consume feed in order to satisfy their energy needs, the excess energy will be converted to fat which act as energy reserves for the chickens (Fouad and El-Senousey, 2014). Although the excessive fat deposition is an unfavorable trait in broiler industry, its organoleptic effects on the flavor of the meat is favorable.…”
Section: Discussionmentioning
confidence: 99%